Minimal residual ascites 3 months after TIPS implantation implicates worse clinical outcomes in patients with cirrhosis - Jim Benjamin Mauz; Lukas Hartl; Andrea Kornfehl; Sarah Lisa Schütte; Paul Hemetsberger; Theresa Müllner-Bucsics; Mathias Jachs; Anja Tiede; Hannah Rieland; Michael Schwarz; Nina Dominik; Georg Kramer; et al. (JHEP Reports)
Background & Aims: Transjugular intrahepatic portosystemic shunt (TIPS) implantation is indicated for recurrent/refractory ascites in patients with cirrhosis. The prognostic impact of residual minimal ascites after TIPS implantation has not yet been investigated. Methods: We included patients with cirrhosis undergoing covered TIPS implantation for refractory ascites in Vienna (2000–2022) and Hannover (2009–2021) with available abdominal ultrasound 3 months after TIPS insertion (3M). The patients were followed up for further decompensation and transplant-free mortality. Two distinct competing risk regression models (Adjusted model I and Adjusted model II) were performed to determine the prognostic impact of no vs. minimal ascites at 3M. Results: Overall, 292 patients with male predominance (71.7%) and mostly alcohol-related liver disease (71.7%) were included. At 3M, n = 105 (36.0%) patients showed no ascites on abdominal ultrasound, whereas n = 82 (28.1%) exhibited minimal and n = 105 (36.0%) moderate/severe ascites. The portal pressure gradient after TIPS implantation was similar in the three groups (median 7 mmHg; p = 0.311). Patients with no or minimal ascites had comparable Model for End-Stage Liver Disease and Freiburg Index of Post-TIPS Survival scores at baseline and 3M. Competing risk regression models showed that minimal ascites (vs. no ascites) was an independent predictor of further decompensation (Adjusted model I: adjusted subdistribution hazard ratio [aSHR], 1.69; 95% CI, 1.03–2.77; p = 0.038; Adjusted model II: aSHR, 1.76; 95% CI, 1.07–2.88; p = 0.026) and transplant-free mortality (Adjusted model I: aSHR, 1.76; 95% CI, 1.08–2.88; p = 0.024; Adjusted model II: aSHR, 1.73; 95% CI, 1.05–2.82; p = 0.030). Conclusions: Patients with residual minimal ascites at 3M remain at higher risk for further decompensation and transplant-free mortality compared with those with no residual ascites. Impact and implications: This study evaluated the prognostic relevance of residual ascites grades in patients with advanced chronic liver disease after TIPS placement. Severe ascites was linked to the worst outcomes, underscoring the need for urgent liver transplantation evaluation. However, even minimal residual ascites significantly increased the risk of further decompensation and transplant-free mortality. These findings suggest that patients with minimal residual ascites will benefit from enhanced post-TIPS clinical monitoring. Further research is warranted to uncover the underlying mechanisms and investigate the potential of targeted interventions to improve outcomes in this vulnerable group.